A review of Dutch elm disease and new prospects for Ulmus americana in the urban environment. Issue 1 (2nd January 2023) - Copeland, Christopher A.; Harper, Richard W.; Brazee, Nicholas J.; Bowlick, Forrest J.
ABSTRACT: American elm ( Ulmus americana ) is an important cultural and historic symbol of the North American landscape. Its graceful form and resilience to harsh growing conditions made it ideal for widespread planting as an urban tree. However, with the initial introduction of Dutch elm disease ( Ophiostoma ulmi ) to the United States in the late 1920ʹs, and the later appearance of the more virulent O. novo-ulmi, American elm populations commenced a sudden and precipitous decline due to mortality associated with Ophiostoma spp. The absence of this tree created a gap in riparian areas of native forests and resulted in a substantial reduction in urban tree canopy cover throughout communities of the United States and Canada. Here we highlight the prevalence of the American elm in the U.S., and the affiliated impacts of Dutch elm disease (DED). We also discuss important factors including mode of DED introduction and transmission, and challenges associated with DED management in the urban environment. Results from ongoing evaluation of putatively resistant American elms are detailed.